2004
DOI: 10.1111/j.1365-2036.2004.02067.x
|View full text |Cite
|
Sign up to set email alerts
|

Wireless capsule endoscopy in patients with obscure gastrointestinal bleeding: a comparative study with push enteroscopy

Abstract: SUMMARYBackground: The identification and treatment of lesions located in the small intestine in obscure gastrointestinal bleeding is always a clinical challenge. Aim: To examine prospectively the diagnostic precision and the clinical efficacy of capsule endoscopy compared with push enteroscopy in obscure gastrointestinal bleeding. Methods: Forty-two patients (22 men and 20 women) with obscure gastrointestinal bleeding (overt bleeding in 26 cases and occult blood loss with chronic anaemia in 16) and normal oes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 29 publications
2
50
1
4
Order By: Relevance
“…CE facilitates effective decision-making regarding subsequent investigations and treatments [4] . Diagnostic yield of CE for OGIB varied between 31% and 91% [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Lema and Ruano-Ravina [32] reviewed the published studies of CE for OGIB and reported that sensitivity ranged from 79% to 95% and specificity from 75% to 100%.…”
Section: Indicationsmentioning
confidence: 99%
“…CE facilitates effective decision-making regarding subsequent investigations and treatments [4] . Diagnostic yield of CE for OGIB varied between 31% and 91% [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Lema and Ruano-Ravina [32] reviewed the published studies of CE for OGIB and reported that sensitivity ranged from 79% to 95% and specificity from 75% to 100%.…”
Section: Indicationsmentioning
confidence: 99%
“…We must remember that capsule endoscopy is not completely reliable (6,8,14,15), although it does enable us to explore the whole small intestine. Several studies have shown the superiority of this technique over other traditional approaches, including barium radiology.…”
Section: Discussionmentioning
confidence: 99%
“…As a diagnostic method, capsule endoscopy has presented us with a new challenge, namely the choosing of the therapeutic or confirmatory approach to lesions found (6,7,9).…”
Section: Introductionmentioning
confidence: 99%
“…CE has a high diagnostic yield in OGIB, facilitates effective decision-making regarding subsequent investigations and treatments .Diagnostic yield of CE for OGIB varied between 31% and 91% (Adler et al,2004;Costamagna et al,2004;Ell et al,2002;Ersoy et al,2006;Ge et al,2004;Golder et al,2006;Hartmann et al 2003Hartmann et al ,2005Lewis & Swain,2002;Mata et al,2004;Panazio et al,2004;Scapa et al,2002;Saurin et al,2003;Saperas et al,2007;Van gossum et al,2003;Voderholzer et al,2003). The published studies of CE for OGIB were reviewed and reported that sensitivity ranged from 79% to 95% and specificity from 75% to 100% (Varela Lema & Ruano-Ravina, 2008 ).…”
Section: Obscure Gi Bleedingmentioning
confidence: 99%